THE EFFECT OF PAY LATER USE ON IMPULSE PURCHASES OF GLOBAL BRAND PRODUCTS IN BATAM CITY - Fasha, Andina; Shen, Jocelyn Gabrielle; Kesumahati, Erilia (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
Buy Now Pay Later (BNPL) services have gained immense popularity, especially among younger generations such as Gen Z, due to their easy accessibility and flexible payment options. This study explores the impact of BNPL usage on impulse buying behavior, specifically in Batam, Indonesia. This study aims to examine the influence of BNPL usage on impulse buying of global brand products, focusing on understanding the psychological mechanisms, such as self-control, that mediate this relationship. A quantitative research design using SmartPLS 4 was adopted. Data were collected through questionnaires distributed to 230 respondents in Batam who actively use BNPL services. The study is relevant to Indonesia’s growing digital financial landscape. However, since the data were collected only from Batam City, the findings do not sufficiently represent BNPL users across Indonesia. The sample calculation used the theory of Hair et al. This study found that BNPL promotion, social influence, and perceived ease of use significantly influence self-control, influencing impulse buying behavior. Furthermore, self-control was identified as a mediator between BNPL services and impulse buying. This study provides insights for BNPL service providers to develop responsible marketing strategies and highlights the need for financial literacy programs to help consumers manage impulse buying behavior. This study was limited to respondents in Batam and focused primarily on a young population, which may not fully represent the broader BNPL consumer base. This study used only the application.